A Study On Cultivating Learning Culture As A Strategy For Organizational Success - Premi, Harish; Pahwa, Mohit (Gyan Management Journal, 2020)
Success is a subjective and  comprehensive  concept and so is the learning. This paper is aimed at  studying the importance of learning culture and to identify the drivers to cultivate learning culture and  further to develop a conceptual framework as a strategy for Organization Success. Today’s business  environment is becoming more and more dynamic and complex impacted by various factors such as  rapid  change  in  technology,  creative  destruction  and  reinvention.  The  fast  paced  technology  is  affecting every industry and area of life, and work is no exception to this. To become successful in  changing  times,  work  must  become  more  meaningful  and  must  include  constant  learning.  An  organization learning culture is referred to ‘a set of norms and values that define the functioning of an  organization which motivates individuals as well as the organization for continuous learning’. The  present study aims to indentify the variables that affect the learning culture in an organization. Based  on the literature  review and subsequent study, six main independent  variables are indentified i.e.  growth oriented mindset, lead by example, reflective mindset, test-and-learn culture, feedback and  reward mechanism, while the mediating variables are increased job satisfaction, lower turnover rates,  increased profitability, profits and flexibility and ‘Organization Success’ is taken as the dependent  variable. This study is significant for an organization to indentify the most valuable driver that can  contribute to cultivate a learning culture as a strategy. After all, it’s the learning of each and every  individual which helps an organization to grow not only in terms of physical resources but also in terms  of intellectual capabilities which is the only fundamental requirement to achieve the success in real  terms.
Keywords: Keywords: Learning Culture; Continuous Learning; Growth Oriented Mindset; Test and-learn culture; Reflective Mindset